Decoding Misconceptions in Thermochemistry: Insights from the Four-Tier Diagnostic Test - Novita, Widya; Winda, Eka (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: The purpose of this study was to determine whether or not there were student misconceptions and their causes, as well as to determine the percentage of student misconceptions on thermochemistry material measured using the Four-Tier Diagnostic Test Instrument. Methodology: This research is a descriptive study where the sample in this study was taken using purposive sampling technique. The subjects in this study were students of grade XI and XII of State Islamic High School 1 Pekanbaru. Data collection techniques used in this study were the Four-Tier Diagnostic Test, observation, interviews and documentation. Main Findings: The study revealed 4% of grade XI and 13% of grade XII students had misconceptions in thermochemistry. Misconceptions were higher in grade XII for basic concepts (19.7%) and reaction types (13.4%), while grade XI struggled more with enthalpy calculations (6.3%). Understanding remained limited across key concepts. Novelty/Originality of this study: It can help increase teachers' insight in the teaching and learning process, so that teachers are more aware of the explanation of the material that sometimes makes students wrong and experience misconceptions. In addition, teachers can also provide follow-up to students if misconceptions occur.